MENGATASI KRISIS MENTAL SPIRITUAL MELALUI PENDEKATAN TASAWUF DI DALAM DUNIA PENDIDIKAN - Mustang, Abubakar (STAI YAPIS Takalar, 2022)
Impact from shift value inside modern life often seen in the middle life society, no except in the world of education, it seems already start realized. Various effort has conducted for return spiritual mental stability. One of them is through approach Sufism in the world of education. Sufism lift come back to surface from those who don't civilized Becomes civilized, of material inclination towards material and spiritual balance. All form downturn return treated with serving fresh water that delivers to destination more life clear and directed. In principle Sufism is an educational model that teaches ma'rifat to Allah, which is marked with belief that gone worshiped god except Allah. Sufism introduce and offer therapy education psychological, get used to multiply worship and life simple in framework bring closer self to God through level purification self, which in turn always feel presence of God within every situation as mandated in draft courtesy. With such circumstances, will radiate manners and morals that can guard condition psychological between teachers and students. Master applies wise to students, and students are proud, respectful, and always prejudiced good to the teacher, in turn next external education will bring stock balance Among ability ornate intellectual with a tough spiritual mentality.